Coordinated regulation of pH alkalinization by two transcription factors promotes fungal commensalism and pathogenicity - Xinhua Huang; Guangsheng Chen; Lei Wu; Yun Zou; Luyao Zhang; Shanshan Li; Kunlin Li; Zaijie Jiang; Yuping Zhang; Xiaoqing Chen; Winnie Shum; Jianbiao Dai; et al. (Nature Communications)
Abstract As a clinically relevant opportunistic human fungal pathogen, Candida albicans is able to rapidly sense and adapt to changing microenvironments within the host, a process that is essential for its successful invasion and survival. Although studies have shown that the transcription factor Stp2 is the master regulator of environmental alkalinization, accumulating evidence supports a clear involvement of other participants in this adaptation process. Here, following a large-scale genetic screen, we identify the transcription factor Dal81 as an uncharacterized positive regulator of pH alkalinization in C. albicans. Dal81 influences the protein levels of Stp2. A mutant lacking DAL81 also fails to alkalinize both in vitro and in the phagolysosome, and this defective phenotype is further enhanced by deleting both factors in most cases. Notably, our results demonstrate that Dal81 physically interacts with Stp2 to co-regulate the expression of a broad set of downstream target genes related to metabolism of organic acids, oxoacids, carboxylic acids and amino acids. This coordinated regulation mode is required for the alkalinization process and plays a role in modulating commensalism and pathogenicity of C. albicans. Taken together, our findings elucidate the cooperative function of Dal81 with Stp2 in the nucleus to orchestrate the expression of downstream genes required for the survival and propagation of C. albicans in the host.